Access Inequalities in the Artistic Labour Market in the UK: A Critical Discourse Analysis of Precariousness, Entrepreneurialism and Voluntarism. Issue 4 (22nd December 2017) - Samdanis, Marios; Lee, Soo Hee
Abstract : This paper investigates the roles played by social enterprise and social activism in mitigating access inequalities in the artistic labour market in the UK. Our analysis focuses on underpaid internships as a primary form of access inequalities. By employing critical discourse analysis, this study contrasts the discourses of entrepreneurialism and voluntarism advocated by the government and social enterprises, with the counter‐discourse of precarity advanced by social activists. The central argument is that precarity is not simply an innate characteristic of artistic labour, but is also a social construct and discourse which is directly linked to social class and the experience of less privileged creative workers.